Thailand 4.0 in World Politics: The 5S Foreign Affairs Strategy - Subboonrueng, Hongpha; Bunyavejchewin, Poowin (Thai Journal of East Asian Studies, 2019)
This article examines how the Thai government, led by General Prayut Chan-o-cha, conducted the nation’s foreign policy as part of a wider policy orientation and its vision of Thailand 4.0. It found that the Prayut government outlined its foreign policy strategy, called “5S foreign affairs strategy,” comprising: security, sustainability, standard, status, and synergy. Its 5S strategy echoed the Thai foreign policy tradition, widely recognized for its flexibility in a wind of change. Despite the list of diplomatic failures during the government’s first year in office, the government’s foreign-policy maneuvering in world politics could manage the external environment to be more favorable for Thailand’s economic development.